Supporting students’ engagement with teachers’ feedback: the role of students’ school identification - Carvalho, C.; Santos, N. N.; António, R.; Martins, D. (Educational Psychology, 2021)
This study explored the link between teachers’ feedback and students’ behavioural engagement with school identification. Using a sample of 2534 students from 6th to 12th school year, we examined whether their perceptions about teachers’ feedback were related to their behavioural engagement and mediated by their school identification. We also explore whether this relation was moderated by students’ year of schooling and by the type of secondary course they were enrolled and the differences of latent means between these groups. Results confirmed the expected mediation: teachers’ feedback was associated with an increased behavioural engagement via increased school identification. Only the type of students’ secondary course moderated this relation. Students in the 12th year perceived that their teacher used less effective feedback and felt lower school identification than students in the early years of schooling. These finding illustrated the underlying mechanism through which teachers’ feedback affect students’ behavioural engagement with school.